1999
DOI: 10.1200/jco.1999.17.3.846
|View full text |Cite
|
Sign up to set email alerts
|

Pamidronate Reduces Skeletal Morbidity in Women With Advanced Breast Cancer and Lytic Bone Lesions: A Randomized, Placebo-Controlled Trial

Abstract: Treatment with 90 mg of pamidronate as a 2-hour intravenous infusion every 4 weeks in addition to hormonal therapy significantly reduces skeletal morbidity from osteolytic metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
292
1
16

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 563 publications
(316 citation statements)
references
References 23 publications
7
292
1
16
Order By: Relevance
“…In recent years bisphosphonates have become important in the management of cancer-induced bone disease and are now well established in the management of patients with multiple myeloma and bone metastases secondary to breast cancer (Paterson et al, 1993;Berenson et al, 1996;Hortobagyi et al, 1996;Diel et al, 1998;McCloskey et al, 1998;Theriault et al, 1999). Randomized controlled trials in patients with breast cancer have demonstrated that clodronate and pamidronate reduce skeletal morbidity and improve quality of life (Paterson et al, 1993;Hortobagyi et al, 1996;Kanis et al, 1996).…”
mentioning
confidence: 99%
“…In recent years bisphosphonates have become important in the management of cancer-induced bone disease and are now well established in the management of patients with multiple myeloma and bone metastases secondary to breast cancer (Paterson et al, 1993;Berenson et al, 1996;Hortobagyi et al, 1996;Diel et al, 1998;McCloskey et al, 1998;Theriault et al, 1999). Randomized controlled trials in patients with breast cancer have demonstrated that clodronate and pamidronate reduce skeletal morbidity and improve quality of life (Paterson et al, 1993;Hortobagyi et al, 1996;Kanis et al, 1996).…”
mentioning
confidence: 99%
“…Bisphosphonates (BPs) have proven useful in the treatment of bone metastases in breast cancer patients and have improved their quality of life in a number of clinical trials (Theriault et al, 1999;Lipton et al, 2000). In the first years of BP use, the efficacy of these substances was thought to lie entirely in the antiproliferative and apoptotic effects on osteoclasts (Hughes et al, 1995;Selander et al, 1996).…”
mentioning
confidence: 99%
“…Bisphosphonates reduce the skeletal morbidity rate in breast cancer patients with bone metastases by up to 40 -50% (Paterson et al, 1993;Body et al, 1998;Hortobagyi et al, 1998;Theriault et al, 1999;Body, 2001) and they can decrease the number and the extent of bone metastases in animal models of tumour-induced osteolysis (Hughes et al, 1995;Hiraga et al, 2001) as well as in patients treated in the adjuvant setting (Coleman, 2002;Powles et al, 2002).…”
mentioning
confidence: 99%